Evaluación de la Incidencia de Mosca Blanca (Trialeurodes vaporariorum) en el Cultivo de Tomate Riñón (Solanum lycopersicum Mill) Bajo Invernadero Mediante el Método Etológico, en la Parroquia San Roque, Cantón Antonio Ante de la Provincia de Imbabura - López Oviedo, William German (2018)
SUMMARY The main problem of the cultivation of tomato kidney (Solanum lycopersicum M) in the Parish of San Roque has been determined to be of high incidence of whitefly attack (Trialeurodes vaporariorum), caused by monoculture and poor practice of cultural work, all this is due to their desire to generate economic resources. To determine the incidence of the attack of whitefly (Trialeurodes vaporariorum) an ethological control was used consisting of traps made with yellow plastic of 0.50m wide and 1m long impregnated with a glue product, one was placed at the rate of 1000 m2 of culture, monitoring and data collection were made every 15 days. The producers of the zone showed that they have a low productivity of the crop caused by the high rate of attack of this insect. It was concluded that due to the sum of different factors, the greenhouse number one has a moderate attack of this pest; greenhouse number two has a high rate of attack and very low performance in its productivity and greenhouse number three does not present losses in its production due to the indiscriminate use of pesticides. It is advisable to carry out good practices of cultural work as well as the authorities should worry a bit more about the agriculture of the sector and the Técnica de Babahoyo University carries out more research in the area on this and other topics.